((-m²-20) – (6m² – 3n+8) ( - m square - 2n) - (6msquare - 3n + 8)

Question

((-m²-20) – (6m² – 3n+8)
( - m square - 2n) - (6msquare  - 3n + 8)

in progress 0
Abigail 2 weeks 2021-09-11T13:33:11+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-11T13:34:40+00:00

    Answer:

    = -5m² + 3n – 28

    Step-by-step explanation:

    = (m²-20) – (6m² – 3n+8)

    =  m² – 20- 6m² + 3n – 8

    = m² – 6m² +3n -20-8

    = -5m² + 3n – 28

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )